Biofertilizing potential of feather hydrolysate produced by indigenous keratinolytic Amycolatopsis sp. MBRL 40 for rice cultivation under field conditions. (April 2017) - Tamreihao, K.; Devi, Laishram Jaya; Khunjamayum, Rakhi; Mukherjee, Saikat; Ashem, Roshan Singh; Ningthoujam, Debananda S.
Abstract: Extracellular keratinase-producing strain Amycolatopsis sp. MBRL 40 exhibited antifungal activity against four important rice fungal pathogens and plant growth promoting traits such as indole 3-acetic acid (IAA) production and phosphate (P) solubilization. The strain could produce IAA in the degraded feather medium (3 µg/ml) and increased production was observed when the medium was supplemented with 0.2% tryptophan (7 µg/ml). The strain could solubilize significant amounts of tricalcium P (117 µg/ml). Rice seeds treated with MBRL 40 showed higher germination percentages and vigor indices, and enhanced seedling growth over control under gnotobiotic conditions. Under field conditions, rice plants grown in presence of dried hydrolysate pellet (P), hydrolysate filtrate (S) and feather hydrolysate with bioinoculant (B+F) exhibited significantly enhanced growth and higher number of tillers per plant over plants grown in the absence of urea (C-). However, P treated plants did not have enhanced growth in all the parameters in comparison to plants treated with S and B+F. Rice grown in presence of B+F was found to exhibit better growth over plants grown in presence of P and S. Rice grown in presence of urea (C+) and B+F showed similar levels of growth promotion. Highlights: Amycolatopsis sp. MBRL 40 exhibited antifungal activity against rice phytopathogens. The strain showed positive results IAA production and phosphate solubilization. Rice seeds treated with strain showed significantly higher growth over control. Rice plants grown with feather hydrolysates showed enhanced growth over control plants Feather hydrolysate with bioinoculant and urea showed similar levels of rice growth.